IMPLEMENTASI KEPEMIMPINAN KENEGARAWANAN DALAM PEMAJUAN KEPEMIMPINAN NASIONAL - Sudiarso, Aries; Tuasikal, Husein (JAB (Jurnal Akuntansi & Bisnis), 2019)
This research aims to review the implementation of national leadership in statesmanship leadership indonesian president to run for the leadership of their ir. Was up to the leadership of president dr .S.B yudhoyono , especially in statesmanship of leadership in the national leadership. Of statesmanship leadership to operated who found the concept of regeneration leadership, education and training of legal certainty and the leadership and government institutions. Of the three leadership conception statesmanship leaderships do attempt to implementation national leadership to the furtherance of which made statesmanship leadership must be able to follow any change of progress in the field of national leadership .Shall be a national of leadership needs to be answered by the leader of the country. When this was conducted then happen to the steady improvement of national leadership and able to answered all the global dynamic.Â Keywords : Statesmanship Leadership and National leadership